Building general practice training capacity in rural and remote Australia with underserved primary care services: a qualitative investigation - Louise Young; Raquel Peel; Belinda O'Sullivan; Carole Reeve (BMC, 2019)
Abstract Background Australians living in rural and remote areas have access to considerably fewer doctors compared with populations in major cities. Despite plentiful, descriptive data about what attracts and retains doctors to rural practice, more evidence is needed which informs actions to address these issues, particularly in remote areas. This study aimed to explore the factors influencing General Practitioners (GPs), primary care doctors, and those training to become GPs (registrars) to work and train in remote underserved towns to inform the building of primary care training capacity in areas needing more primary care services (and GP training opportunities) to support their population's health needs. Methods A qualitative approach was adopted involving a series of 39 semi-structured interviews of a purposeful sample of 14 registrars, 12 supervisors, and 13 practice managers. Fifteen Australian Medical Graduates (AMG) and eleven International Medical Graduates (IMG), who did their basic medical training in another country, were among the interviewees. Data underwent thematic analysis. Results Four main themes were identified including 1) supervised learning in underserved communities, 2) impact of working in small, remote contexts, 3) work-life balance, and 4) fostering sustainable remote practice. Overall, the findings suggested that remote GP training provides extensive and safe registrar learning opportunities and supervision is generally of high quality. Supervisors also expressed a desire for more upskilling and professional development to support their retention in the community as they reach mid-career. Registrars enjoyed the challenge of remote medical practice with opportunities to work at the top of their scope of practice with excellent clinical role models, and in a setting where they can make a difference. Remote underserved communities contribute to attracting and retaining their GP workforce by integrating registrars and supervisors into the local community and ensuring sustainable work-life practice models for their doctors. Conclusions This study provides important new evidence to support development of high-quality GP training and supervision in remote contexts where there is a need for more GPs to provide primary care services for the population.